Chronic pain and local pain in usually painless conditions including neuroma may be due to compressive proximal neural lesion - Macionis, Valdas (Frontiers in Pain Research, 2023)
It has been unexplained why chronic pain does not invariably accompany chronic pain-prone disorders. This question-driven, hypothesis-based article suggests that the reason may be varying occurrence of concomitant peripheral compressive proximal neural lesion (cPNL), e.g., radiculopathy and entrapment plexopathies. Transition of acute to chronic pain may involve development or aggravation of cPNL. Nociceptive hypersensitivity induced and/or maintained by cPNL may be responsible for all types of general chronic pain as well as for pain in isolated tissue conditions that are usually painless, e.g., neuroma, scar, and Dupuytren's fibromatosis. Compressive PNL induces focal neuroinflammation, which can maintain dorsal root ganglion neuron (DRGn) hyperexcitability (i.e., peripheral sensitization) and thus fuel central sensitization (i.e., hyperexcitability of central nociceptive pathways) and a vicious cycle of chronic pain. DRGn hyperexcitability and cPNL may reciprocally maintain each other, because cPNL can result from reflexive myospasm-induced myofascial tension, muscle weakness, and consequent muscle imbalance- and/or pain-provoked compensatory overuse. Because of pain and motor fiber damage, cPNL can worsen the causative musculoskeletal dysfunction, which further accounts for the reciprocity between the latter two factors. Sensitization increases nerve vulnerability and thus catalyzes this cycle. Because of these mechanisms and relatively greater number of neurons involved, cPNL is more likely to maintain DRGn hyperexcitability in comparison to distal neural and non-neural lesions. Compressive PNL is associated with restricted neural mobility. Intermittent (dynamic) nature of cPNL may be essential in chronic pain, because healed (i.e., fibrotic) lesions are physiologically silent and, consequently, cannot provide nociceptive input. Not all patients may be equally susceptible to develop cPNL, because occurrence of cPNL may vary as vary patients' predisposition to musculoskeletal impairment. Sensitization is accompanied by pressure pain threshold decrease and consequent mechanical allodynia and hyperalgesia, which can cause unusual local pain via natural pressure exerted by space occupying lesions or by their examination. Worsening of local pain is similarly explainable. Neuroma pain may be due to cPNL-induced axonal mechanical sensitivity and hypersensitivity of the nociceptive nervi nervorum of the nerve trunk and its stump. Intermittence and symptomatic complexity of cPNL may be the cause of frequent misdiagnosis of chronic pain.